Papua Students Media Literacy in Facing Actions of Racism in Indonesia - Chontina Siahaan; Nahria Nahria; Manotar Tampubolon (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
News of the racist incident that occurred at the Papuan Student Dormitory in Surabaya on August 16, 2019, then spread so quickly and massively, especially through social media. The purpose of the research was to find out the media literacy of Papuan students related to acts of racism. This study uses a qualitative method with data collection techniques consisting of observation, in-depth interviews, documents and focus group discussion. The results showed that racist is an act of abuse against ethnic Papuans who violate human rights and a racist is an act that violates religious teachings.  Racists are considered to be degrading acts of Papuans as beings created by God who have human rights brought from birth regardless of racial, ethnic, and physical differences and no religion allows the act of harassing or insulting fellow human beings.